Outcome of extra mucosal single interrupted layer (EMSIL) ileo-ileal anastomosis in urinary diversions during open radical cystectomy - Abdul Rouf Khawaja; Mujahid Ahmad Mir; Arshi Beg; Shahid M. Baba; Mohammad Saleem Wani; Arif Hamid (African Journal of Urology, 2023)
Abstract Background We intended to assess the outcome of extra-mucosal single interrupted layer ileo-ileal anastomosis for bowel re-approximation in open radical cystectomy with urinary diversions. Methods This is a prospective study of patients who had extra-mucosal ileo-ileal intestinal anastomosis following radical cystectomy and urinary diversion at our institution from January 2018 to April 2021. Data was collected from patient medical records and analyzed by using SPSS Statistics for Windows version 25.0. Data was expressed as a mean ± standard deviation (SD) or median for continuous variables, whereas frequency and percentage were used to express qualitative data. Operative time and anastomosis time, blood loss, hospitalization duration, and time taken for the return of bowel activity were studied. Perioperative complications were noted down. Results Fifty-nine patients were selected for our study. Urinary diversion was achieved in the form of ileal conduit (IC) in 49 patients and orthotopic neobladder (ONB) in 10 patients following radical cystectomy. The mean operative duration was 263.8 ± 48.9 min and the mean anastomosis time was 17.3 ± 5 min. Thirty-eight patients needed blood transfusion (0.97 ± 0.79 units per patient). The mean (± SD) time taken for the return of bowel activity was 84.6 ± 10 h and the average (± SD) post-operative hospital stay was 12.6 ± 3.1 days. There was no anastomotic leak or any other major intestinal complication in any of our patients. Conclusions Extra-mucosal single layer ileo-ileal anastomosis for bowel re- approximation is safe and is associated with acceptable and easily managed complications in patients following radical cystectomy and urinary diversion.